Involvement of patients' perspectives on treatment with noninvasive ventilation in patients with chronic obstructive pulmonary disease—A qualitative study. Issue 1 (5th July 2017) - Christensen, Helle Marie; Huniche, Lotte; Titlestad, Ingrid L
Abstract : Aims and objectives: To clarify chronic obstructive pulmonary disease patients' perspectives on treatment with noninvasive ventilation and develop management strategies for the treatment based on these perspectives. Background: The effect of treating chronic obstructive pulmonary disease patients with noninvasive ventilation is well‐documented, as is the problem of patient difficulties in tolerating the treatment. Knowledge of how patients with chronic obstructive pulmonary disease experience and evaluate treatment with noninvasive ventilation is limited; therefore, more information of patient perspectives is needed to develop treatment practices in respiratory medicine. Method: This study is based on critical psychological practice research. Design: A co‐researcher group comprising diverse health professionals was set up and headed by the principal researcher. The group convened seven times over 12 months to develop new management strategies based on patients' perspectives on noninvasive ventilation. Health professionals contributed with experience‐based perspectives, and the researcher contributed with data from participant observation in the department and semi‐structured interviews with 16 patients and four relatives. Results: Interviews revealed that patients with chronic obstructive pulmonary disease regarded noninvasive ventilation treatment positively even though they experienced discomfort and anxiety. Patients' perspectives revealed that patients with chronic obstructive pulmonary disease conduct their everyday lives with chronic obstructive pulmonary disease looking at chronic obstructive pulmonary disease as a basic life condition rather than an illness. This approach had a major impact on chronic obstructive pulmonary disease patients' attitudes to noninvasive ventilation treatment and hospitalisation. Conclusion: Investigation of patient perspectives generated results that were highly productive in facilitating multidisciplinary collaboration and in developing and sustaining new management strategies. Critical psychological practice research facilitated ongoing development of clinical practice related to noninvasive ventilation treatment. Relevance to clinical practice: Focus on patients' perspectives in treatment with noninvasive ventilation resulted in the development of new management strategies regarding patient care, joint ward rounds, and in addition, one room at the ward, to which a nurse was assigned, was designated for chronic obstructive pulmonary disease patients treated with noninvasive ventilation.